PREVALENCE OF HEPATITIS B AND HEPATITIS C VIRUS COINFECTION IN HEMODIALYSIS UNIT, Dr. SARDJITO GENERAL HOSPITAL, YOGYAKARTA - , SUNITHA S.SASIKUMAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Because of the shared modes of transmission, hepatitis B virus (HBV) and hepatitis C virus (HCV) co-infection is not uncommon in highly endemic areas and among subjects with a high risk of parenteral infections. In Yogyakarta, HBV/HCV coinfection may be rising concern which we are unaware of. In this research, we calculate the prevalence of hepatitis B and hepatitis C virus co-infection in haemodialysis unit, Dr. Sardjito General Hospital, Yogyakarta. Objective : The objective of this study is to obtain and observe the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) co-infection at the haemodialysis unit in the Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Methods : This is a cross sectional descriptive study which is done at the hemodialysis unit, Dr. Sardjito General Hospital, Yogyakarta. The data of patients undergoing haemodialysis were taken. For instance, their sex, race, and age. Results : The prevalence of hepatitis B and hepatitis C virus co-infection in the haemodialysis unit in Dr. Sardjito General Hospital, Yogyakarta is 17.42%. Conclusion : Based on the study, out of 137 subjects who undergo hemodialysis, 24 patients were diagnosed with positive hepatitis B and hepatitis C co-infection.